Numerical Simulation of Bird Strike with Varied L/D Ratio in Hemispherical-ended Cylinder Bird Model Using Coupled Eulerian Lagrangian Method - Yuniarti, Endah; Sitompul, S Afandi; Warsiyanto, B Aji (Universitas Andalas, 2023)
This research studies the numerical simulation of the finite element method for bird strike using a hemispherical-ended cylinder bird model with varying length-to-diameter (L/D) ratio, namely 1.4; 1.5; 1.6; 1.7; 1.8; 1.9; and 2.0. Birds are modelled with elastic, plastic, and hydrodynamic behaviour. The bird model uses the Coupled Eulerian-Lagrangian (CEL) method with impact speeds of 100 ms-1, 200 ms-1, and 300 ms-1. The simulation results show that the Hugoniot pressure value is around 15-36 times higher than stagnation pressure in L/D 1.4; 14-36 times in L/D 1.5; 13-30 times in L/D 1.6; 12-32 times in L/D 1.7; 12-26 times in L/D 1.8; 13-30 times in L/D 1.9; and 13-29 times in L/D 2.0. It was found that the highest Hugoniot and stagnation pressure were in L/D 1.5 and 1.8, while the lowest Hugoniot and stagnation pressure were in L/D 2.0 and 1.5, respectively. In addition, the error of the numerical results of the average Hugoniot and stagnation pressure value compared to the analytic was 2.9% and 7%, respectively.Â